Frontispiece: A New Potent Inhibitor of Glycogen Phosphorylase Reveals the Basicity of the Catalytic Site - Mamais, Michael; Degli Esposti, Alessandra; Kouloumoundra, Virginia; Gustavsson, Thomas; Monti, Filippo; Venturini, Alessandro; Chrysina, Evangelia D.; Markovitsi, Dimitra; Gimisis, Thanasis (Chemistry – A European Journal, 2017)
Glycogen phosphorylase (GP) plays a key role in glucose regulation. The design and synthesis of a new potent inhibitor of GP is described. By exploiting its optical properties, it is shown that, due to an extended hydrogen bonding network, the local pH in the GP catalytic site is higher than 12. For the full story, see the Communication by A. Venturini, E. D. Chrysina, D. Markovitsi, T. Gimisis et al. on page 8800 ff.
Keywords: acridone based inhibitors; glycogen phosphorylase; optical spectra; quantum chemistry; X-ray crystallography